1966
DOI: 10.1126/science.152.3722.653
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin: Production by a Particulate Fraction of Rat Kidney

Abstract: An erythropoietic factor was extracted with hypotonic phosphate buffer from the kidneys of hypoxic rats. Normal rat serum enhanced the activity of this factor, which is associated with the light mitochondrial fraction. The data suggest that the renal factor is not physiologically active unless it interacts with a serum carrier or activator, or that the factor may be an enzyme which produces erythropoietin from some serum substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

1968
1968
1981
1981

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…It is known that the kidney produces an erythropoietic factor that in teracts with a plasmatic substratum to form erythropoietin [1,11]. In the rabbit this factor accumulates at least partly in the spleen and is then re leased into the blood circulation, both in the first few hours after bleeding and in the subsequent evolution of the anaemia [6][7][8].…”
mentioning
confidence: 99%
“…It is known that the kidney produces an erythropoietic factor that in teracts with a plasmatic substratum to form erythropoietin [1,11]. In the rabbit this factor accumulates at least partly in the spleen and is then re leased into the blood circulation, both in the first few hours after bleeding and in the subsequent evolution of the anaemia [6][7][8].…”
mentioning
confidence: 99%
“…A renal erythropoietic factor (erythrogenin) has been found in the nuclear (13) and light mitochondria1 (14) fractions of the kidney and is capable of generating erythropoietic activity when reacted with a plasma substrate. Therefore, it is possible that the epithelial cell may be a site in the kidney where erythrogenin acts on a substrate to generate ery thropoietin.…”
mentioning
confidence: 99%
“…L ewis et al [5] have identified the presence of erythro-stimulant fac tors in the urine of anaemic patients; in particular, in addition to erythro poietin, an erythropoietic factor has also been found, possessing certain characteristics similar to those of the renal factor studied by Contrera and Gordon [1] and by Z anjani et al [13], since it gives rise to the pro duction of erythropoietin if incubated with serum of normal rabbits.…”
mentioning
confidence: 93%